Past, present and future of nucleic acids electrochemistry - Palecek, Emil (Talanta, 2002)
Electrochemistry of nucleic acids was discovered about 40 years ago. During the first 15 years electrochemistry brought early evidence of DNA premelting and polymorphy of the DNA double helix. At present electrochemical methods working with stationary electrodes are able to detect DNA at attomol and in some cases, even at lower levels. A great progress in the development of electrochemical sensors for DNA hybridization and DNA damage achieved in recent years suggests that these sensors may soon become important tools in medicine and other areas of practical life of the 21st century.